Rancang Bangun Sistem Otomasi untuk Indikator Penentuaan Jarak Objek Benda - Syafriwel Syafriwel; Muhammad Fadlan Siregar; Jhoni Hidayat; Ayu Fitriani (Universitas Batanghari Jambi, 2022)
The distance to an object can be known without having to measure it with a meter. The design of this tool can determine an object with a certain position in the form of an indicator that is displayed automatically. An object is a part of determining indicators that can be used as receiving media for the final boundary reflection. With this tool, you can accurately determine the distance to objects without using conventional measuring instruments. The method used is to design the equipment and then test the tool. This tool works when there is input in the form of a password code via the keypad, and if the code or password is entered correctly, the microcontroller will provide high input to the relay to activate this solenoid which is run with the Arduino IDE software so that the microcontroller can detect keypad input properly, the delay is applied to activate the solenoid, by using the proximity sensor we know the accurate limit is for this tool to be able to read the distance of the object provided that the closest distance to the object is 0.5 meters and the farthest is 2 meters with a response time interval of 0.07 seconds to 2.10 seconds, this equipment controlled by Arduino with a listing program that has been set to read objects at a certain distance, with a reading distance. the program listing uses a sound indicator as an output with a sound indicator at a distance of approximately 2 meters.